The Role of Play Based Learning in Early Childhood Development - Sitorus, Riska Wulandari; Siregar, Khairi Permana; Sari, Ratih Irma (Educia Journal, 2025)
This study investigates how play-based learning activities improve the cognitive and social along with emotional and physical development of early childhood students. The research design uses both interviews with teachers and parents as well as direct observation to explore how play-based learning activities help develop every aspect of development. The research indicates that through play children become better at learning new information while also developing creativity skills and critical thinking abilities as well as social and emotional competencies through empathy and emotional control and they are able to learn physically through better motor skills. The research study delivers practical solutions for implementing play in scheduled curriculum alongside key implementation strategies for resolving related problems. The existing research gap enables this study to provide complete knowledge about effective methods to implement play-based learning within early childhood education for children's comprehensive development. Finding in this investigation demonstrate the necessity to combine developmental progress with academic achievements while following present learning system measurements of achievement.